2021
DOI: 10.1088/1361-6668/ac1c14
|View full text |Cite
|
Sign up to set email alerts
|

Fully-staggered-array bulk Re-Ba-Cu-O short-period undulator: large-scale 3D electromagnetic modelling and design optimization using A-V and H-formulation methods

Abstract: The development of a new hard x-ray beamline I-TOMCAT equipped with a 1 m long short-period bulk high-temperature superconductor undulator (BHTSU) has been scheduled for the upgrade of the Swiss Light Source at the Paul Scherrer Institute. The very hard x-ray source generated by the BHTSU will increase the brilliance at the beamline by over one order of magnitude in comparison to other state-of-the-art undulator technologies and allow experiments to be carried out with photon energies in excess of 60 keV. One … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…In 2019, Calvi et al experimentally demonstrated that a 5-period BHTSU10 model shown in figure 13(c) could obtain an on-axis field B 0 of 0.85 T at 6 mm magnetic gap after FC magnetization with ∆B s = 7 T at 10 K and that further increase of ∆B s would result in a premature quench [107]. Numerical simulations were later carried out by Hellmann et al with COMSOL H-formulation for understanding the complex correlation between B 0 and design parameters and by Zhang et al with ANSYS A-V formulation based backward computation method for optimizing the on-axis field integrals in a 10-period staggered-array 3D BHTSU model [110][111][112]. In 2021, it was experimentally demonstrated that a 10-period BHTSU10 model could obtain an on-axis field B 0 of ∼1.54 T @ 10 K at 4 mm magnetic gap and that a subcooling from 10 K to 8 K could help to freeze the trapped magnetic flux in GdBCO bulks, resulting in a long decay time constant of 3.2 years [3].…”
Section: Staggered-array Bulk Hts Planarmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, Calvi et al experimentally demonstrated that a 5-period BHTSU10 model shown in figure 13(c) could obtain an on-axis field B 0 of 0.85 T at 6 mm magnetic gap after FC magnetization with ∆B s = 7 T at 10 K and that further increase of ∆B s would result in a premature quench [107]. Numerical simulations were later carried out by Hellmann et al with COMSOL H-formulation for understanding the complex correlation between B 0 and design parameters and by Zhang et al with ANSYS A-V formulation based backward computation method for optimizing the on-axis field integrals in a 10-period staggered-array 3D BHTSU model [110][111][112]. In 2021, it was experimentally demonstrated that a 10-period BHTSU10 model could obtain an on-axis field B 0 of ∼1.54 T @ 10 K at 4 mm magnetic gap and that a subcooling from 10 K to 8 K could help to freeze the trapped magnetic flux in GdBCO bulks, resulting in a long decay time constant of 3.2 years [3].…”
Section: Staggered-array Bulk Hts Planarmentioning
confidence: 99%
“…In 2005, Alexeev et al first adopted the FEM software ANSYS for calculating the magnetic field in a helical SCU designed for a MIR-FEL experiment [11]. Further studies based on ANSYS were reported for the magnetic and mechanical design study of Nb 3 Sn planar SCU [77,151] and staggered-array bulk HTSU [111,112,152]. In 2010, Majoros et al first adopted the FEM software FLUX 3D for simulating the magnetic fields in a 3D Nb 3 Sn helical SCU model [22].…”
Section: Modelling Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the progress in co-simulation methodology, the circuit model of a 10 kV cable system was modeled in Matlab/Simulink, while its field model modeled in ANSYS did not take into account the superconducting properties [20]. To cope with the HTS simulation in ANSYS, the resistivity adaptation algorithm was first explored in 2005 [21][22][23], while the E-J relation was not introduced until 2021 using an iteration approach [24][25][26][27]. Combining the field-circuit coupling methods [28][29][30], more work is needed to develop new models for an accurate system characterization, which is also applicable to other multi-physics software.…”
Section: Introductionmentioning
confidence: 99%
“…Based on COMSOL Multiphysics, the indirect coupling approach in the partial differential equation (PDE) module [36] and the moving grid approach in the AC/DC module [37,38] are extensively utilized. Based on ANSYS, the A-V formulation is implemented to optimize the superconducting electromagnetic device [39].…”
Section: Introductionmentioning
confidence: 99%